Efektivitas Pemanfaatan Lingkungan dalam Meningkatkan Hasil Belajar Mata pelajaran IPA Pada Siswa SMP Negeri 13 Bontoa - Nurbaya; Hanida Listiani; Nur Mustaqimah (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2022)
Subjects in science, with learning resources in the environment, can be considered in the teaching and learning process. Based on observations at SMPN 13 Bontoa, the use of the environment has not been maximized. The purpose of this study was to compare the learning outcomes of students who were taught about the interactions of living things using the environment as a learning resource to those who were not. Experimental research in the form of a quasi-experimental design was carried out from February to April 2021. Data were obtained from a posttest and observations. Descriptive analysis and inferential analysis techniques were used to process the data. The results of the control class showed 31 students, or 54.83%, in the medium category. The experimental class, totaling 31 people, is 54.84% of the high category. The results of the t-test showed that H0 was rejected, H1 was accepted with count = 30.57, and ttable = 2.00 with dk = 60. This study showed higher student learning outcomes by utilizing the environment as a learning resource. For future research, it is expected to be possible to examine student learning motivation and creativity related to the use of the environment as a learning resource.